Monitoring of the bioencapsulation of aprobiotic Phaeobacter strain in the rotifer Brachionus plicatilis using denaturing gradient gel electrophoresis - Pintado, José; Pérez-Lorenzo, María; Luna-González, Antonio; González Sotelo, Carmen; Prol García, María Jesús; Planas, Miguel (Aquaculture, 2010)
6 figuras, 5 tablas The bioencapsulation of the probiotic bacteria Phaeobacter 27-4 in the rotiferBrachionus plicatilis was monitored by culture methods and denaturing gradient gel electrophoresis (DGGE) of PCR-amplified 16 S rDNA. In a first experiment, the permanence of the probiotic bacteria in clear water and green water was studied. Phaeobacter 27-4 added to the water of the tanks (107 CFU ml-1) remained at levels around 106 CFU ml-1 for 72 h and was not affected by the presence of the algae added (Isochrysis galbana, 105 cells ml-1). The DGGE fingerprints showed a temporal predominance of the probiont in the water and the presence of bacteria belonging to the Flavobacteria, γ-proteobacteria, and Sphingobacteria groups. ATenacibaculumstrain became predominant when Phaeobacter 27-4 decline, and at the end of the experiment, bacterial profiles became similar to the initial ones with predominance of bacteria belonging to the Oceanospirillaceae family. Three different ways of bioencapsulation of the probiont in the rotifer were assayed: E24, addition of Phaeobacter 27-4 for 24 h during the enrichment with I. galbana; E3, addition of Phaeobacter 27-4 during the last 3 h of the enrichment with I. galbana and E3+, with the bioencapsulation done in a separated step, after the 24 h enrichment with I. galbana, being the rotifers filtered, washed and transferred into tanks containing Phaeobacter 27- 4 in seawater, and maintained for 3 h. The result showed that the presence of the algae was not determinant in the effectiveness of the bioencapsulation and the probiont was bioencapsulated in all cases in the first 3 h to a level of 102 cfu rotifer-1. When the rotifers with the bacteria bioencapsulated were transferred to green-water tanks and kept in the conditions used in turbot larvae rearing, Phaeobacter 27-4 maintained levels close to 102 CFU rotifer-1 for 48 h in the case of E24 and E3, and for 24 h in the case of E3+, a period of time sufficient to the larvae to graze on them and to incorporate the probiotic. The ...